SIMULATION OF INDIVIDUAL TELERADIOGRAPHIC INDICATORS USING THE “CEPHALOMETRICS FOR ORTHOGNATHIC SURGERY” METHOD IN UKRAINIAN YOUNG WOMEN WITH A VERY BROAD FACE TYPE - Nesterenko, Ye.A.; Shevchuk, Yu.G.; Shinkaruk-Dykovytska М.М.; Lysenko, S.A.; Chugu, T.V. (World of Medicine and Biology, 2023)
In the course of the study, in Ukrainian young women with an orthognathic bite and with a very wide face type, reliable regression models of teleroentgenometric indicators used in the “Cephalometrics for orthognathic surgery” method were built and analyzed (all indicators were divided into 3 groups according to the method of Dmitriev M. O.). With a coefficient of determination higher than 0.6, out of 33 possible, 5 reliable indicator models were built, which were included in the second and third groups, depending on the indicators of the first group (R²= from 0.616 to 0.789), and out of 19 possible – 13 indicator models, which were included in the third group depending on the indicators of the first and second groups (R²= from 0.612 to 0.991).